Food Allergies and Anaphylaxis in the Community: The School Nurse's Role. (January 2023) - Keller, Aimee; Morse, Brenna; Conroy, Michelle
Food allergy prevalence in the United States has been increasing among school-aged children. Many community-based pediatric caregivers (e.g., camp staff, sports coaches) are not trained to prevent, recognize, or manage allergic reactions due to a lack of available training and standard policies on this topic. Epinephrine is the first-line of treatment for severe allergic reactions and delayed administration of this medication can result in poor health outcomes and death. School nurses may use their knowledge and expertise to educate community-based pediatric caregivers on allergy topics. Professional practice projects can be utilized by school nurses to help improve allergy and anaphylaxis confidence and knowledge among community-based pediatric caregivers. By educating community members on anaphylaxis management, it can improve health outcomes for children of the school community and result in saved lives.